Extracorporeal CO2 Removal: The Minimally Invasive Approach, Theory, and Practice*. Issue 1 (January 2019) - Duscio, Eleonora; Cipulli, Francesco; Vasques, Francesco; Collino, Francesca; Rapetti, Francesca; Romitti, Federica; Behnemann, Tim; Niewenhuys, Julia; Tonetti, Tommaso; Pasticci, Iacopo; Vassalli, Francesco; Reupke, Verena; et al.
Abstract : Objectives: Minimally invasive extracorporeal CO2 removal is an accepted supportive treatment in chronic obstructive pulmonary disease patients. Conversely, the potential of such technique in treating acute respiratory distress syndrome patients remains to be investigated. The aim of this study was: 1) to quantify membrane lung CO2 removal (VCO2ML ) under different conditions and 2) to quantify the natural lung CO2 removal (VCO2NL ) and to what extent mechanical ventilation can be reduced while maintaining total expired CO2 (VCO2tot = VCO2ML + VCO2NL ) and arterial PCO2 constant. Design: Experimental animal study. Setting: Department of Experimental Animal Medicine, University of Göttingen, Germany. Subjects: Eight healthy pigs (57.7 ± 5 kg). Interventions: The animals were sedated, ventilated, and connected to the artificial lung system (surface 1.8 m 2, polymethylpentene membrane, filling volume 125 mL) through a 13F catheter. VCO2ML was measured under different combinations of inflow PCO2 (38.9 ± 3.3, 65 ± 5.7, and 89.9 ± 12.9 mm Hg), extracorporeal blood flow (100, 200, 300, and 400 mL/min), and gas flow (4, 6, and 12 L/min). At each setting, we measured VCO2ML, VCO2NL, lung mechanics, and blood gases. Measurements and Main Results: VCO2ML increased linearly with extracorporeal blood flow and inflow PCO2 but was not affected by gas flow. The outflow PCO2 was similar regardless of inflow PCO2 and extracorporeal blood flow, suggesting that VCO2ML was maximally exploited in each experimental condition. Mechanical ventilation could be reduced by up to 80–90% while maintaining a constant PaCO2 . Conclusions: Minimally invasive extracorporeal CO2 removal removes a relevant amount of CO2 thus allowing mechanical ventilation to be significantly reduced depending on extracorporeal blood flow and inflow PCO2 . Extracorporeal CO2 removal may provide the physiologic prerequisites for controlling ventilator-induced lung injury. Abstract : Supplemental Digital Content is available in the text.